2023
DOI: 10.1111/ddg.14987
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous reactions following COVID‐19 vaccination assessed by dermatologists: a single‐institutional study in Germany

Abstract: Summary Background and objectives Cutaneous reactions following COVID‐19 vaccination have been frequently described, whereas larger case series by dermatologists are lacking. This study assesses SARS‐CoV‐2 vaccination‐associated skin reactions, severity, treatment, course, eliciting vaccines, allergy test results and tolerance to revaccination. Patients and methods Single‐institutional, non‐interventional study of dermatologists assessing cutaneous manifestations in 83 patients in Germany. Results 93 reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Similarly, studies on the cutaneous reactions following COVID-19 vaccination found that these reactions included exacerbation of known skin diseases indicating that vaccinations may trigger immunological diseases in those patients who are already predisposed to them. 4 To the best of our knowledge, this is the first report of AD and psoriasis flare-ups after monkeypox vaccine administration.…”
Section: Dear Editormentioning
confidence: 80%
See 2 more Smart Citations
“…Similarly, studies on the cutaneous reactions following COVID-19 vaccination found that these reactions included exacerbation of known skin diseases indicating that vaccinations may trigger immunological diseases in those patients who are already predisposed to them. 4 To the best of our knowledge, this is the first report of AD and psoriasis flare-ups after monkeypox vaccine administration.…”
Section: Dear Editormentioning
confidence: 80%
“…1 During the largest outbreak of monkeypox beginning in 2022 and affecting almost exclusively men who have sex with men with multiple sexual partners, 2 the administration of the Jynneos vaccine was authorized for the high-risk population. 1 In clinical trials, common mild side effects have been described with a latency time ranging from 0 to 21 days: redness and itching at the injection site (40−60%), 3 similar to the "COVID-arm" observed after COVID-19 vaccine, 4 and several systemic reactions were frequently observed after vaccinations: fatigue, headache, and nausea. Adverse events with serious outcomes were uncommon.…”
Section: Dear Editormentioning
confidence: 96%
See 1 more Smart Citation
“…In our review, 98 cases have been collected, also during treatment with omalizumab [ 95 , 96 , 101 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 ]. Of note, two types of urticaria may be distinguished: immediate and delayed, with the first as the most common, as reported by Wang et al in their monocentric real-life study investigating cutaneous manifestations following vaccination [ 207 ] ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%